(untitled) (UNED Research Journal, 2018)
Silver nanoparticles (AgNPs) are widely used in industrial and medical applications. However, there is a growing concern about the potentialities of AgNPs to induce genotoxicity and DNA damage in humans. In this study, genotoxic and histopathological effects of AgNPs were investigated in mice using two well-characterized genetic assays: mouse bone marrow micronuclei (MN) and mouse sperm morphology assays. Swiss albino mice (total N=18) were exposed to varying concentrations (3,000mg/Kg, 4,000mg/Kg, 5,000mg/Kg and 6,000mg/Kg) of AgNPs for 5 consecutive days and observed for 30 days afterwards. Distilled water and colchicine were used as negative and positive controls, respectively. The MN assay showed that the frequency of micronuclei induction increased with AgNP concentration. Statistically significant differences (p<0,05) were observed for the micronucleus frequency in the blood erythrocytes in all the test concentrations. Sperm head morphology assay also revealed various types of abnormal sperm head morphology and there was statistically significant increase in frequency of sperm abnormalities. Histopathological profiles of the liver also showed enlarge sinusoids, irregular portal tract, and dose-dependent vacuolation. These results suggest that AgNPs is genotoxic and represent a serious health risk to human heatlh.